2017
DOI: 10.1177/0081246317715351
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and its relation to personality psychopathology in a South African female forensic context

Abstract: There is a paucity of research about personality pathology among female offenders. This study aims to address this gap in the forensic psychology empirical base by examining the relationship between female psychopathy, as measured by the Psychopathy Checklist–Revised, and personality disorders, as measured by the Millon Clinical Multiaxial Inventory-III in a South African forensic context. Participants included 108 purposively sampled female offenders incarcerated in South Africa. The Kruskal–Wallis H test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In Norway, the rate is 10 times lower than in the United States; only severe offenders are imprisoned, and nearly half the prison population meets criteria for psychopathy (Sullivan & Kosson, 2006). A recent study of incarcerated women in South Africa also found psychopathy to be particularly associated with Cluster B PDs (Botha, Louw, & Loots, 2017).…”
Section: Antisocial Personality Disorder Psychopathy and Criminal Bmentioning
confidence: 91%
“…In Norway, the rate is 10 times lower than in the United States; only severe offenders are imprisoned, and nearly half the prison population meets criteria for psychopathy (Sullivan & Kosson, 2006). A recent study of incarcerated women in South Africa also found psychopathy to be particularly associated with Cluster B PDs (Botha, Louw, & Loots, 2017).…”
Section: Antisocial Personality Disorder Psychopathy and Criminal Bmentioning
confidence: 91%
“…Although focused predominantly on male offenders, research underscores the relationship between personality disorders, particularly psychopathy, and offending behaviour [8][9][10][11]. Worldwide, psychopathy rates among incarcerated female offenders range from 9 to 15.5%, contrasting with approximately 31% in males [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Levenson et al [18] distinguish between primary and secondary dimensions of psychopathy, with primary focusing on selfish, uncaring, and manipulative attitudes and secondary emphasizing impulsivity and a self-defeating lifestyle. Previous research links psychopathy to antisocial and offending behaviours [19][20][21], particularly violent, serious and chronic offences [8,11,21]. Female offenders in South Africa commonly engage in economic, aggressive, and violent offences [2,4,8,22] with environmental variables (i.e., poverty) [8,23], social factors (i.e., social exclusion and lack of policing) [11,24] and the normalisation of violence [11,25] often cited as contributing factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations